2014
DOI: 10.1111/ced.12455
|View full text |Cite
|
Sign up to set email alerts
|

Does poor sleep quality affect skin ageing?

Abstract: This study indicates that chronic poor sleep quality is associated with increased signs of intrinsic ageing, diminished skin barrier function and lower satisfaction with appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
114
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 21 publications
6
114
0
6
Order By: Relevance
“…Moreover, this significant association remained unchanged through multiple linear regression analyses that controlled for confounding factors. Oyetakin-White et al (12) evaluated the effect of chronic poor sleep quality on the skin condition in 60 healthy Caucasian women, and found that the poor sleepers had significantly higher levels of TEWL and that good sleepers had 30% greater barrier recovery compared with poor sleepers after a tape-stripping procedure. Our results are consistent with those of our previous study, and the chronic decrease in barrier function may be caused by an accumulation of the temporal decrease in recovery capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this significant association remained unchanged through multiple linear regression analyses that controlled for confounding factors. Oyetakin-White et al (12) evaluated the effect of chronic poor sleep quality on the skin condition in 60 healthy Caucasian women, and found that the poor sleepers had significantly higher levels of TEWL and that good sleepers had 30% greater barrier recovery compared with poor sleepers after a tape-stripping procedure. Our results are consistent with those of our previous study, and the chronic decrease in barrier function may be caused by an accumulation of the temporal decrease in recovery capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Because the effects are similar to those seen as a symptom of aging, it is possible that sleep debt may increase the severity of age-related chronic disorders. Oyetakin-White et al have shown that chronic poor sleep quality was significantly associated with the conditions of the skin, such as higher TEWL levels (12). Moreover, an acute 42-h period of sleep deprivation led to the impaired recovery capacity of skin barrier function after a tape-stripping procedure and to increases in inflammatory cytokines (13).…”
mentioning
confidence: 99%
“…The current outcomes add to the growing body of literature on the relationship between negative self-perceptions of physical appearance and insomnia by providing an understanding of a potential mechanism which may underlie this relationship 1,4,6 . To provide support for these preliminary results, future research should examine the present research questions amongst a sample meeting diagnostic criteria for insomnia.…”
mentioning
confidence: 86%
“…Similarly, poorsleepers appear to show greater self-perceived dissatisfaction with aspects of their facial appearance (i.e. complexion) and skin-age compared to normal-sleepers 6 . Therefore, it seems that poor sleep and symptoms of insomnia confound an individual's judgements of physical self-perception.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, a recent report suggested that there exists a relationship between sleep quality and facial sebum levels in women with acne vulgaris (Bilgic et al 2016). In another study unrelated to computer use, Caucasian women who were good sleepers had significantly lower intrinsic skin aging scores that poor sleepers (Oyetakin-White et al 2015). Because it has been suggested that high computer use can lead to sleep disturbances, in the current study questions related to sleep quality were given to all subjects.…”
Section: Conclusion and Discussionmentioning
confidence: 87%